The Penta Helix Model in Tourism Village Development: A Case Study of Samida, Garut Regency - Sumarna, Eeng; Geohansa, Ahmad; Kania, Ikeu; Akbar, Gugun Geusan; Ulumudin, Aceng (Ilomata International Journal of Social Science, 2025)
This study investigates the application of the Penta Helix Model as a framework for developing tourism villages through multi-stakeholder collaboration. The model involves five key actors: government, academia, businesses, communities, and media, each contributing to the planning and implementation of tourism initiatives. Integrating these sectors, the model promotes inclusive, innovative, and sustainable tourism development. The research focuses on the Samida Tourism Village in Garut Regency and employs a qualitative case study approach. The data collection involved in-depth interviews, field observations, and document analysis to identify the drivers and challenges of stakeholder collaboration. The results show that effective stakeholder coordination strengthens destination attractiveness and stimulates innovation. However, the study finds that maintaining consistent stakeholder engagement remains a significant challenge. The findings emphasize that active community involvement is essential for preserving cultural authenticity and ensuring long-term sustainability. This research contributes to understanding collaborative governance in rural tourism and highlights the importance of policy frameworks that foster synergy across sectors. Future studies should explore practical strategies to enhance stakeholder commitment and address obstacles in implementing the Penta Helix Model.